Covid 19 and its Impact on Transport Contracts - Maadaoui, Nadjia (Journal of Legal Studies and Researches, 2021)
Various countries of the world witnessed the spread of the new Corona virus, which was reflected in contractual relations, including land and air transport contracts and even maritime transport, which are considered the economic lifeline and the nerve of the commodity circulation of services. Termination of these contracts, or the dissolution of responsibility for not fulfilling the obligations resulting from those contracts, when their implementation is impossible, or at least requesting the financial balance of the contract if its implementation becomes cumbersome and harmful to one of the parties.